Reduction of liver metastasis stiffness improves response to bevacizumab in metastatic colorectal cancer - Shen, Ying; Wang, Xiaohong; Lu, Junyan; Salfenmoser, Martin; Wirsik, Naita Maren; Schleußner, Nikolai; Imle, Andrea; Freire Valls, Aida; Radhakrishnan, Praveen; Liang, Jie; Wang, Guoliang; Muley, Thomas; et al. (Cancer cell, 2020)
Tumors are influenced by the mechanical properties of their microenvironment. Using patient samples and atomic force microscopy, we found that tissue stiffness is higher in liver metastases than in primary colorectal tumors. Highly activated metastasis-associated fibroblasts increase tissue stiffness, which enhances angiogenesis and anti-angiogenic therapy resistance. Drugs targeting the renin-angiotensin system, normally prescribed to treat hypertension, inhibit fibroblast contraction and extracellular matrix deposition, thereby reducing liver metastases stiffening and increasing the anti-angiogenic effects of bevacizumab. Patients treated with bevacizumab showed prolonged survival when concomitantly treated with renin-angiotensin inhibitors, highlighting the importance of modulating the mechanical microenvironment for therapeutic regimens.